(untitled) (Bangladesh Journal of Medical Education, 2026)
Background: In medical education correlation of theoretical and practical knowledge is most important aspect of learning. Hence the teaching should also be done in integrated manner, where different subjects unify to teach a relevant topic in more effective manner. Objective: This study aimed to identify the major issues influencing the implementation of integrated teaching in MBBS curriculum 2021 and to suggest recommendations to solve these. Methods: A cross-sectional study was conducted among 337 MBBS students (2021 curriculum) and 176 faculty members from government and non-government medical colleges in Bangladesh. Institutes were selected through stratified sampling, and participants through random sampling. Data were collected via pretested questionnaires and in-depth interviews. Feedback on integrated teaching was analyzed using frequency, percentage, and appropriate statistical tests, while thematic analysis was applied to interview findings. Results: Students strongly supported the need for training of the educational workforce (mean 4.11±0.77), while their views on integrated teaching for OSPE were neutral (mean 2.99±1.12). Non-government respondents generally provided higher ratings, with significant group differences in areas such as teaching hours, student-teacher ratio, adequacy of workforce, resources, and training needs (p<0.05). Faculty interviews revealed dissatisfaction with selected topics, limited training and administrative support, lack of interdepartmental coordination, and inconsistent session formats. Recommendations included enhanced faculty training, stronger administrative initiatives, better coordination, and establishment of medical education units to support effective implementation of integrated teaching. Conclusion: The study highlights strengths and challenges of integrated teaching in Bangladesh’s MBBS curriculum, stressing workforce preparation and the need for collaboration and support. BJME:Vol.-17, Issue-01, January, 2026:3-18